Electroencephalography microstates imbalance across the spectrum of early psychosis, autism, and mood disorders - Anton Iftimovici; Angela Marchi; Victor Férat; Estelle Pruvost-Robieux; Eléonore Guinard; Valentine Morin; Yannis Elandaloussi; Arnaud D’Halluin; Marie-Odile Krebs; Boris Chaumette; Martine Gavaret (European Psychiatry, 2023)
Abstract